Pengaruh Kepercayaan, Kemudahan Dan Kualitas Informasi Transaksi Terhadap Keputusan Pembelian Pada Olshopshopee (Studi Kasus Pada Mahasiswa Program Studi Manajemen Fakultas Ekonomi Dan Bisnis Universitas Islam Malang Angkatan 2018) - Ristya Irianti Cahyaningrum; N. Rachma; M. Hufron (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis study aims to determine and analyze the influence of trust, convenience, and quality of information on online purchasing decisions at Shopee. This research is an explanatory research type, with a quantitative approach. The research method used is multiple regression analysis. The sample used in this study used the Maholtra formula with purposive sampling technique, namely the sampling technique based on certain considerations that are considered suitable with the characteristics of the specified sample to be sampled and obtained 85 respondents as a sample of 1014 respondents as a population.The results of this study indicate that partially there is a significant influence between trust in purchasing decisions, convenience has a significant effect on purchasing decisions, and information quality has a significant effect on online purchasing decisions at the online shopee. While the simultaneous test results show that trust, convenience and quality of information affect online purchasing decisions at online shopee shops. Keywords: Trust, convenience, and quality of information and purchase decisions.